Perancangan Sistem Akuntansi Penggajian ‘Si Warna’ Di Pt Harapan Kurnia Textile Indonesia - Reza Angelika; Tiris Sudrartono; Rini Suwartika Kusumadiarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research conducted at PT Harapan Kurnia Textile Indonesia aims to produce accurate attendance information, fast, effective and efficient payroll management, provide financial reports for companies and payslips for employees appropriately. To identify the problems faced, primary and secondary data collection as well as qualitative descriptive approaches were used in this study. The method for developing software that uses waterfall with HTML to create pages on websites and databases is MYSQL. The results of this study show that the payroll management process has run well but still uses Microsoft Excel manually which is prone to errors. So to overcome these problems, an application design was made in the form of Flowmap, ERD and DFD and designed a payroll accounting system with web-based PHP programming language code. The conclusion of this study is that the color becomes a problem solver that will help HRD and financial staff in managing payroll to be faster, more precise and efficient and produce accurate payslips and financial statements. The advice given by the author is to conduct computer training payroll applications, perform system maintenance to prevent damage / errors in the system and back up data so that data remains safe if the computer is damaged. Keywords : Design, Accounting System, Payroll